Co-Operative Credit Delinquency: Identification of Factors Discriminating Defaulters - Michael, Justin Nelson (Indian Journal of Finance, 2011)
Co-operative movement dawned in India a century ago to eradicate indebtedness and to accelerate agricultural production in India. Co-operatives are eminently suited to achieve social, economic changes in rural India. However, credit risk is acute in a co-operative credit system, predominantly manifested in the short-term credit. Delinquency of co-operative credit is the object of enquiry for many committees and researches. Mounting overdues at the level of Primary Agricultural Co-operative Banks (PACB) contribute to the accumulation of Non-performing Assets (NPA) in the Central Co-operative Banks (CCB). Willful default has been identified as the main reason for mounting overdues. This empirical study of defaulters of co-operative credit has examined the factors discriminating default of co-operative credit, which subsequently increase NPA. Univariate Analysis and Discriminant Function analysis were carried out to identify the factors. Such identification of factors discriminating credit default is crucial to reduce credit delinquency in the co-operative credit system.